Modelling of three-phase uniform symmetrical sampling digital PWM for power converter - Mekhilef, Saad; Rahim, N.A.; Omar, A.M. (2004)
A mathematical approach of modelling and analysing three-phase pulse width modulation (PWM) is presented. The three-phase flyback converter required a unique pattern of PWM to optimise the power transfer in the magnetic circuit used in the converter. The three-phase PWM is generated digitally based on uniform symmetrical sampling technique using Xilinx chip. The generated PWM pattern is able to reduce the low order of harmonic components present in the input AC supply. Although software simulation could simulate the PWM pattern, it does not represent the exact pattern as been generated digitally. The mathematical approach used is to model the PWM pattern exactly as been created digitally. The proposed mathematical technique could also be used to analyse any digital PWM. The result of the mathematical analysis on the PWM pattern could be used to study the characteristics of the pattern such as maximum and minimum value of duty cycle, pulse width, turn-on time, turn-off time and modulation index. To verify the validity of the proposed technique, the results obtained from the mathematical model, experimental and simulation using PSpice were compared.